Strategies for Resolving Tenurial Conflicts in Conservation Forest after the Enactment of the Omnibus Law: Case Study from Gunung Lengkuas, Bintan Regency, Indonesia - Kurniawan, Aprianto; Jumiati , Ipah Ema; Indah, Diani (Manunggal Halim Jaya, 2025)
The conservation area of KSA/KPA Gunung Lengkuas has undergone significant land-use changes due to extensive soil excavation, leaving behind open pits and ponds. The construction of an asphalt road cutting through the area has further increased accessibility, thereby intensifying competition among various stakeholders to control and manage the land. This situation has triggered persistent tenurial conflicts. The purpose of this study is to analyze strategies for resolving tenurial conflicts in the KSA/KPA Gunung Lengkuas Conservation Forest, Bintan Regency, Riau Islands Province, following the enactment of the Omnibus Law. The research employs conflict resolution theory by Hugh Miall, Oliver Ramsbotham, and Tom Woodhouse, encompassing strategies of competition, accommodation, collaboration, avoidance, and compromise/negotiation. A qualitative descriptive case study approach was applied, with data obtained from eight key informants through observation, interviews, and documentation. Data analysis involved source triangulation, SWOT analysis, and internal–external matrix evaluation. Findings indicate that conflict resolution in this conservation forest is best achieved through collaboration strategies, supported by conservation partnership programs and community empowerment. However, current approaches remain ineffective, particularly in addressing third-party land rights within residential zones. The study recommends enhanced government–community engagement, legal clarity on land tenure, and sustained socialization efforts to prevent future tenurial conflicts.